Effect of 12-Week Low-intensity Exercise on Interleukin-2, Interferon-gamma, and Interleukin-4 Cytokine Production in Rat Spleens - Eun-Ju Choi; Wi-Young So (Journal of Men's Health, 2018)
Background and Objective: High-intensity exercise has been linked to immunity; however, the relationship between low-intensity exercise and the immune system is unclear. In this study, the effects of exercise on cytokine production in T helper 1 (interleukin-2 [IL-2] and interferon-gamma [INF-g]) and T helper 2 cells (interleukin-4 [IL-4]) in spleens were investigated.